Bronenosets Potemkin . Battleship Potemkin - Eisenstein, Sergei (Sovkino, 1925)
Incomplete: opening credits are missing Based on historical events, the movie tells the story of a mutiny on the battleship Potemkin in 1905. What started as a protest strike when the crew were given rotten meat for dinner ended in a riot. The sailors raised the red flag and tried to ignite the revolution in their home port Odessa.